Reversible Thermochromic Polymeric Thin Films Made of Ultrathin 2D Crystals of Coordination Polymers Based on Copper(I)‐Thiophenolates. (11th December 2017) - Troyano, Javier; Castillo, Oscar; Martínez, José I.; Fernández‐Moreira, Vanesa; Ballesteros, Yolanda; Maspoch, Daniel; Zamora, Félix; Delgado, Salome
Abstract: A one‐pot reaction between Cu(BF4 )2 · x H2 O and 4‐mercaptobenzoic acid in acetone or methanol gives rise to the formation of lamellar microcrystals of two Cu(I)‐thiophenolate‐based coordination polymers (CPs) with the formulas [CuCT] n (1 ) (CT = 4‐carboxy‐thiophenolate) and [CuMCT] n (2 ) (MCT = 4‐methoxycarbonyl‐thiophenolate). Both1 and2 show a reversible luminescent thermochromic behavior upon cooling, changing their color from pale yellow to green to orange in the case of1, and from pale orange to green in the case of2 . It is shown that the lamellar character of these crystals, which exhibit micrometer lateral dimensions and sub‐micrometer/nanometer thicknesses, allows processing them with an organic polymer such as polyvinylidene difluoride (PVDF) to form thermochromic1 @PVDF and2 @PVDF thin films. These thermal stimuli‐responsive thin films are freestanding, free of macroscopic defects, and robust under mechanical bending stress, opening up the possibility to use them in, for example, 2D imaging sensor films. Abstract : Fabrication of reversible thermochromic composite thin films has been achieved by integration of crystalline 2D crystals of coordination polymers, which exhibit micrometer lateral dimensions and sub‐micrometer/nanometer thicknesses allowing an efficient dispersibility in polyvinylidene difluoride. These thermal stimuli‐responsive composite thin films are flexible, freestanding, free of macroscopic defects, and robust under mechanical bending stress.